Characterization of CsI(Tl) Crystals and Implementation of tools for the CALIFA calorimeter at FAIR - Sousa, Tomás Correia (2023)
Tese de mestrado, Engenharia Física , 2023, Universidade de Lisboa, Faculdade de Ciências